2017
DOI: 10.1177/1464884916689277
|View full text |Cite
|
Sign up to set email alerts
|

Is audience engagement worth the buzz? The value of audience engagement, comment reading, and content for online news brands

Abstract: Online audience engagement, such as rating or sharing news, commenting or creating content, can enhance users’ loyalty toward online news brands. Yet recently, uncertainties have been discussed within journalism research and practice concerning the handling of online comment sections and potential negative influences – caused through comment reading – on news brands. From a brand management perspective, audience engagement and comment reading can affect a brand’s equity. This study investigates the value of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 47 publications
(63 reference statements)
0
27
0
Order By: Relevance
“…As regards social networks, this trend expands to the first hours of the next day and to some analysis. Sharing and liking news are associated with a stronger perceived brand quality, loyalty, and associations (Krebs and Lichska, 2017). The most common interaction is the content syndication – through social media – which contributes to legitimate/spread the story – and the brand – but does not imply a new creation by users.…”
Section: Discussionmentioning
confidence: 99%
“…As regards social networks, this trend expands to the first hours of the next day and to some analysis. Sharing and liking news are associated with a stronger perceived brand quality, loyalty, and associations (Krebs and Lichska, 2017). The most common interaction is the content syndication – through social media – which contributes to legitimate/spread the story – and the brand – but does not imply a new creation by users.…”
Section: Discussionmentioning
confidence: 99%
“…In the virtual brand community, the willingness of customers to participate in the collaborative value creation will be affected by subject factors, environmental factors, brand factors, and perceived value factors [28]. Consumer engagement and comment reading will affect brand equity [29]. Previous research found consumer engagement of brand WeChat account affects relationship quality and consumers' overall purchase intention, and it also mediates the impact of perceived value on the two factors [30].…”
Section: Social Interaction and Sustainable Brand Relationshipmentioning
confidence: 99%
“…Online media engagement, such as participation and behaviors on virtual communities, increases brand loyalty (Krebs & Lischka, 2019; Lin, Chen, & Sung, 2018). The same logic applies to the media industry.…”
Section: Social Media News Engagement and Brand Awarenessmentioning
confidence: 99%